2015
DOI: 10.1007/s12663-015-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Facial Bone Fractures in Ile-Ife, Nigeria: An Update on Pattern of Presentation and Care

Abstract: Aims Traumatic injuries remain a major cause of morbidity, mortality and economic loss worldwide. An audit of maxillofacial injuries presenting and managed at any facility is key to understanding the trends, strategies for prevention and improving outcome of care. We sought to study the pattern and treatment of facial bone fractures managed at the Department of Maxillofacial Surgery, Obafemi Awolowo University Teaching Hospital, Ile-Ife, between 2005 and 2013. Also, to compare these with the pattern in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
26
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 16 publications
(30 reference statements)
12
26
4
Order By: Relevance
“…Several authors have attributed the higher prevalence of mandibular fractures to the mobility and prominence of the bone. [ 2 3 4 6 7 10 14 ] In agreement with similar reports,[ 3 14 16 ] the body of the mandible was the most commonly fractured part of the bone. Furthermore, we found that zygomatic bone was the most commonly fractured bone in the midface.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Several authors have attributed the higher prevalence of mandibular fractures to the mobility and prominence of the bone. [ 2 3 4 6 7 10 14 ] In agreement with similar reports,[ 3 14 16 ] the body of the mandible was the most commonly fractured part of the bone. Furthermore, we found that zygomatic bone was the most commonly fractured bone in the midface.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, majority of the patients in this research were mostly unemployed youths. This view was also shared by some Nigerian authors[ 3 4 14 16 ] and other countries in Sub-Saharan Africa. [ 2 7 ] Rising youth unemployment, rural/urban migration, and attendant economic hardship have spurred many youths into riding MCs for commercial purpose in Nigeria.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Road traffic crash was responsible for most of the mandibular fractures in this study. This is in agreement with the findings of Chrcanovic et al 12 and Oginni et al 13 but in contrast to etiological factors in developed nations, in which assaults and interpersonal violence are the leading causes of mandibular fractures 14 .…”
Section: Discussionsupporting
confidence: 93%